2020
DOI: 10.1177/0022022120944475
|View full text |Cite
|
Sign up to set email alerts
|

Callous-Unemotional Traits Among Children and Adolescents in Asian Cultures: A Systematic Review

Abstract: Considerable evidence now exists for callous and unemotional (CU) traits as markers for a high-risk pathway to child and adolescent conduct problems implicating unique risk processes and treatment needs, but research has been limited largely to Western countries. We review the evidence base related to CU traits in Asian countries that has emerged in recent years, with respect to four key questions. Specifically, are higher CU traits among Asian children and adolescents associated with (1) increased severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 74 publications
2
12
0
Order By: Relevance
“…Thus, these factors should be taken into account when considering the generalizability of findings. Recent evidence in support of cultural influences suggests that the manifestation (Allen et al, 2021) and correlates (Hwang et al, 2020) of callous-unemotional traits in children from East Asian countries may differ from those in Western countries (see Sng et al, 2020). In addition, the educational system of Korea is based on Confucianism, which encourages students to feel a strong sense of obligation to pursue scholastic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these factors should be taken into account when considering the generalizability of findings. Recent evidence in support of cultural influences suggests that the manifestation (Allen et al, 2021) and correlates (Hwang et al, 2020) of callous-unemotional traits in children from East Asian countries may differ from those in Western countries (see Sng et al, 2020). In addition, the educational system of Korea is based on Confucianism, which encourages students to feel a strong sense of obligation to pursue scholastic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Current findings need to be replicated in the primary school setting, given that the secondary school period features increased academic demands and higher expectations for student behaviour and independence in combination with less intensive support from teacherspotentially altering the nature and strength of relationships between CU traits, punishment insensitivity, and academic performance. Finally, given evidence for differences in the presentation and correlates of CU traits in East Asian and Western nations (Allen, Shou, Wang, & Bird, 2020;Sng et al, 2018;Sng, Hawes, Hwang, Allen, & Fung, 2020), and differences in teacher classroom management practices and means of assessing student academic achievement (Lewis, Romi, Qui, & Katz, 2005;Romi, Lewis, & Roache, 2013), there may be cultural variation in the relationships between CU traits, punishment insensitivity, and school grades. Future research should strive to investigate cultural differences in the interplay between CU traits and teacher-child interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Peers may also play a less significant role in East Asian cultures, as studies of East Asian children have not found a significant association between CU traits and deviant peer affiliation (Ang et al, 2015;Chu et al, 2014), whereas there is consistent support for this link in Western samples (Backman et al, 2018). More research is needed to compare Western and Asian countries to provide a better understanding of the implications of cultural differences regarding CU traits and social affiliation (Sng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%